Analysis of the Influence of Work Environment and Job Stress on Employee Performance at PT. PNM Mekaar Surabaya - Khamid, Nurul Khanifa; Suwaji, Rifiki (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study aims to examine the influence of the work environment and job stress on employee performance at PT. PNM Mekaar Surabaya. A quantitative approach was used with multiple linear regression analysis to determine the relationships between the independent variables (work environment and job stress) and the dependent variable (employee performance). Data were collected through questionnaires distributed to 92 employees selected using purposive sampling based on predefined criteria. The findings indicate that both variables significantly affect employee performance, with the work environment having a stronger influence compared to job stress. A conducive work environment was shown to enhance employee motivation, comfort, and efficiency, while manageable levels of job stress could act as a performance driver. However, excessive stress negatively impacts productivity. The study suggests that an integrated strategy focusing on environmental improvements and stress management is essential to optimize employee output and organizational effectiveness. These results provide meaningful insights for human resource practices and future research in the field of employee performance and workplace dynamics.